MOTIVASI MASYARAKAT DESA TELAGA SILABA KECAMATAN AMUNTAI SELATAN TERHADAP PENGOBATAN BACABUT - Siti Faridah (Jurnal Studia Insania, 2014)
This paper describes the phenomenon of mysticism outside of religion, namely ‘Bacabut’ treatment. Named ‘Bacabut’ treatment because this treatment can remove the disease from the body in the form of objects such as gravel, broken glass, leather of walnut, ironwood, or ‘Sagar’ (palm stick). The treatment is performed by a physic who gains strength / magic that comes from the help of supernatural beings in the spirit world which is called ‘friend’ (gampiran). In the middle of the progress of society in every field, the understanding and primitive behavior sometimes still influence their lives. People’s dependence on primitive belief and the power of supernatural mystical and magical, making they are sick to prefer going to psychic / shaman to cure the illness than going to a doctor or a health worker. Psychologically, their motivation for treatment to the ‘Bacabut’ treatment divided to two kinds of intrinsic and extrinsic motivation. The intrinsic motivation consists of their own accord and they would like to know / to try it. There are some extrinsic motivations, such as families’ suggestion, many people who come there for treatment, be sure by seeing the evidence. It’s simple, close and it does not specify rates/cheap.